Unlocking the hidden potential: groundwater zone mapping using AHP, remote sensing and GIS techniques - Shelar R.S.; Nandgude S.B.; Pande C.B.; Costache R.; El-Hiti G.A.; Tolche A.D.; Son C.T.; Yadav K.K. (Taylor and Francis Ltd., 2024)
Groundwater resource problems are increasing development and planning challenges due to climate change and overexploitation, necessitating assessments of their potential and productivity. The study area has been facing a groundwater level decline problem for many years, and these results can help increase the groundwater level in the basaltic rock area. In this research, we have worked on the demarcation and suitability of groundwater potential zones using GIS and Analytical Hierarchical Process (AHP) methods for the Urmodi River Basin. This research prepared eight thematic maps, that is, geomorphology, geology, drainage density, land use/land cover, elevation, lineament density and slope from satellite data and GIS methods, which play a primary factor in determining the proper groundwater potential zones. In this study, every thematic map was allocated weights depending on its specific characteristics and contribution to the groundwater potential capacity. The weights were determined using the AHP method, which considers the comparative significance of every layer about others. This weighting procedure allowed for a comprehensive assessment of the factors influencing groundwater potential in the Urmodi River basin. The resulting groundwater potential map was divided into four classes, that is, good, excellent, moderate, and poor. The study revealed that approximately 22.69% of the basin had excellent groundwater potential, 28.96% had good potential, 25.32% had moderate potential, and 22.92% had poor potential. These study findings suggest that a significant portion of the Urmodi River Basin exhibits good to moderate groundwater potential, indicating promising opportunities for sustainable groundwater utilization in the region. The groundwater potential zone map accuracy is 84% based on the Receiver Operating Characteristic (ROC) method. These results can have implications for sustainable groundwater resources and provide a framework for conducting similar assessments in other regions. The results can be more important for sustainable development goals and helpful in increasing groundwater levels in the area. 2023 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.